Pengolah Citra Dengan Metode Thresholding Dengan Matlab R2014A - Setiawan, Ismail; Dewanta, Wika; Nugroho, Hanung Adi; Supriyono, Heru (Jurnal Media Infotama, 2019)
The development of science related to image processing is increasingly popular these days. The availability of technology to capture images well is now not difficult to find. Digital cameras have developed better with the increase in pixel value that can be produced from the camera's capture. Thresholding is an algorithm proposed in this paper to segment digital images which will then be read as the resulting segmented image. The thresholding method works with several steps, namely converting the RGB image color space to Grayscale, segmenting the image using the thresholding method, carrying out complement operations so that the object has a value of 1 (white), while the background has a value of 0 (black) and performing morphological operations to perfect it. the shape of the object in the binary image resulting from segmentation. The morphological operations carried out are in the form of filling holes, area opening, and erosion. This research uses MATLAB r2014a in developing the model.